Depressive symptoms, thyroid hormone and autoimmunity in a population-based cohort from Sardinia - Delitala, Alessandro P; Terracciano, Antonio; Fiorillo, Edoardo; Orrù, Valeria; Schlessinger, David; Cucca, Francesco (Journal of affective disorders, 2016)
To evaluate the association between depressive symptoms and thyroid autoimmunity, and the effect of thyroid hormone on the risk of depression. We included 3138 individuals from SardiNIA project, none of whom was taking thyroid medication and antidepressants. Thyrotropin (TSH), free thyroxine (FT4), and antibodies against thyroperoxidase (TPOAb) were measured in all the sample. Depressive symptoms were assessed with Center for Epidemiologic Studies Depression Scale (CES-D). We found no association between TPOAb and depressive symptoms and no linear association between TSH or FT4 levels and depressive symptoms. However, individuals in the lowest and highest FT4 quintiles showed a higher CES-D score compared to individuals in the middle quintile. In addition, participants in the lowest and highest FT4 quintiles had an increased risk of CES-D≥16 with odds ratios of 1.44 (95% CI=1.09–1.89) and 1.33 (95% CI=1.01−1.77), respectively. Cross-sectional design of the study. A U-shaped relation was found between FT4 and depressive symptoms: compared to average FT4 values, both high and low thyroid function was associated with more depressive symptoms. Further studies are necessary to determine the exact cause-effect relation of this association. •Mood disorders are not related to antibodies against thyroid.•Free thyroxine has a “U-shaped” relation with depressive symptoms.•Free thyroxine is related to depressed mood also in euthyroid subjects.